Patient compliance with and attitudes towards Health Buddy - Bigelow, James H.; Cretin, Shan.; Solomon, Matthew D.; Wu, Shin-Yi.; Cherry, Julie C.; Cobb, Herb.; O'Connell, Michael; Rand Corporation; RAND Health; Health Hero Network (Santa Monica, CA : RAND, 2000)
This report addresses patient acceptance of a new device called a Health Buddy used to communicate between patients chronically ill with congestive heart failure (CHF) and a health care provider (usually a nurse) in a case management program. Literature sources suggest that frequent monitoring of chronically ill patients can improve outcomes and reduce costs through two mechanisms: 1) physicians can respond quickly (e.g., by adjusting medications) to changes in patient status (e.g., weight gain); and 2) the nurse case manager can educate and motivate the patient to comply better with medical advice (e.g., prescribed medications and dietary restrictions). The Health Buddy is placed in the patient's home, and provides daily monitoring--if the patient responds daily to the short survey it offers. Data on 150 CHF patients from two beta test sites suggest a very high level of acceptance and use of Health Buddy. All these patients received the device and responded to at least one survey. Twenty-three dropped out after responding to only one or two surveys. The handful for whom reasons were given dropped out because they moved out of the area, or changed doctors or health plans, not because they disliked the device. The remainder (127 patients) responded to the surveys almost every day--87 percent of days at one site, 91 percent at the other. Most of them reported that they liked using the Health Buddy and found it very helpful.
Introduction -- Case Management with Health Buddy at the Beta Sites -- Setting up and Learning to Use the Health Buddy -- Patient Compliance with Health Buddy Surveys -- Improvements in Patients' Understanding and Management of the Disease -- Attitudes Towards the Use of the Health Buddy -- Summary Observations.
"RAND Health."
The registered trademark symbol "TM" is superscript following "Health Buddy" in the title.
Includes bibliographical references (p. 33-34).
Also available on the internet via WWW in PDF format.
Keywords: Congestive heart failure -- Nursing -- United States -- Evaluation; Congestive heart failure -- Patients -- United States; Hospitals -- Case management services -- United States; Patient compliance -- United States; Patient monitoring -- United States -- Equipment and supplies